EFFECTIVENESS OF AN EDUCATIONAL INTERVENTION FOR THE PREVENTION OF PERIPHERAL VENOUS CATHETER COMPLICATIONS - Almeida, Ana Carolina Nunes de; Pires, Mirele Herculina; Santana, Isabela de Souza; Salgado, Patrícia de Oliveira; Toledo, Luana Vieira; Parreira, Pedro; Braga, Luciene Muniz (Cogitare Enfermagem, 2022)
Objective: To evaluate the effectiveness of an evidence-based practice educational intervention in preventing peripheral venous catheter complications. Method: observational study with educational intervention for nursing professionals of a hospital in Minas Gerais, Brazil, about flushing, push-pause and locking techniques. Convenience sampling: 181 catheters in the pre-intervention group and 157 in the post-intervention group. The incidence of complications was evaluated and compared by the Chi-square and Fisher’s exact tests. Results: the incidence of complications in the post-intervention group was: 4.5% for obstruction (p=0.000), 10.8% for accidental removal (p=0.265) and 1.9% for phlebitis (p=0.847). The use of the flushing, push-pause and locking techniques resulted in a significant reduction in the incidence of obstruction. Conclusion: the educational intervention enabled updated knowledge and the implementation of flushing, push-pause and locking in nursing practices. The study is a contribution to nursing intervention planning to reduce the occurrence of obstruction.